2021
DOI: 10.1177/07435584211062116
|View full text |Cite
|
Sign up to set email alerts
|

“A Little Bit Closer”: A Mixed Method Analysis of the Effect of the COVID-19 Pandemic on the Lives of Adolescent Parents

Abstract: Using a Family Stress Model framework, we used quantitative and qualitative methods to investigate the impact of the pandemic on Latinx pregnant and parenting adolescents and their families. Participants were 406 adolescents (ages 14–19) in the southwestern U.S. who participated in a school-based relationship education program for pregnant and parenting adolescents. In the quantitative analysis, we compared self-reported mental health (depressive symptoms, worry, parental stress), coparental relationships (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…Our results are consistent with impressions of elevated parent and child stress and mental health difficulties experienced during the pandemic derived from recent cross‐sectional research (Brown, Doom, Lechuga‐Peña, Watamura, & Koppels, 2020; Cameron et al., 2020; Spinelli et al., 2020; Yeasmin et al., 2020). However, these results for families with children in middle‐childhood stand in contrast to findings of two studies of adolescents that suggest the possibility of better adjustment during the pandemic compared to before the pandemic (Astle et al., Under review; Twenge et al., 2020). Although it is possible that adolescents may have experienced some improvements in mental health and well‐being during the pandemic not experienced by younger children and their parents, we point out that the results in one study were mixed, and the respondents in the other study reflected a fairly small, circumscribed subset of adolescents (pregnant/parenting Latinx adolescents).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Our results are consistent with impressions of elevated parent and child stress and mental health difficulties experienced during the pandemic derived from recent cross‐sectional research (Brown, Doom, Lechuga‐Peña, Watamura, & Koppels, 2020; Cameron et al., 2020; Spinelli et al., 2020; Yeasmin et al., 2020). However, these results for families with children in middle‐childhood stand in contrast to findings of two studies of adolescents that suggest the possibility of better adjustment during the pandemic compared to before the pandemic (Astle et al., Under review; Twenge et al., 2020). Although it is possible that adolescents may have experienced some improvements in mental health and well‐being during the pandemic not experienced by younger children and their parents, we point out that the results in one study were mixed, and the respondents in the other study reflected a fairly small, circumscribed subset of adolescents (pregnant/parenting Latinx adolescents).…”
Section: Discussioncontrasting
confidence: 89%
“…Two studies have compared the responses of one sample of adolescent respondents before the pandemic to a similar but different sample during the pandemic: In one study, adolescents during the pandemic reported lower levels of reported depression and loneliness, but higher levels of unhappiness and dissatisfaction with life, compared to other adolescents before the pandemic (Twenge, Coyne, Carroll, & Wilcox, 2020). In the second study, pregnant/parenting Latina adolescents reported somewhat better well‐being during the pandemic compared to counterparts from the same high schools before the pandemic (Astle et al., Under review).…”
Section: Figurementioning
confidence: 94%
“…For example, one study revealed no change in couple relationship satisfaction from shortly before to shortly after the pandemic [ 69 ]. Moreover, another study adopted mix-methods to investigate the influence of the pandemic on adolescent parents [ 3 ]. While the qualitative analysis of 21 adolescent parents revealed more adverse effects of the pandemic, such as economic and health stress [ 3 ], the quantitative analysis showed that the pandemic-period cohort also demonstrated fewer DS, parental PS, more positive coparenting communication, and conflict management than the similar pre-pandemic cohort counterparts from the same school [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study adopted mix-methods to investigate the influence of the pandemic on adolescent parents [ 3 ]. While the qualitative analysis of 21 adolescent parents revealed more adverse effects of the pandemic, such as economic and health stress [ 3 ], the quantitative analysis showed that the pandemic-period cohort also demonstrated fewer DS, parental PS, more positive coparenting communication, and conflict management than the similar pre-pandemic cohort counterparts from the same school [ 3 ]. By adopting mixed methods in a sample with relatively good SES, researchers [ 18 ] found that families still encountered challenging struggles in various life domains from May to July 2020, indicating significant associations between the pandemic’s daily impact and elevated psychological distress for children and parents.…”
Section: Discussionmentioning
confidence: 99%
“…However, other research suggests that the parent–child dyad experienced higher levels of closeness than conflict during the pandemic (Horton et al, 2022). Indeed, some families reported improved relationship‐level outcomes, including closeness (Astle et al, 2022).…”
Section: Individual and Family Functioning During Covid‐19mentioning
confidence: 99%